Effects of Fumanet exercise on Korean older adults with mild dementia. Issue 1 (25th July 2019) - Lee, Sun Mi; Joung, Jaewon; Shin, Sung Hee
Abstract: Aim: This study aimed to examine the effects of Fumanet exercise on cognitive function, walking ability, and depression in older adults with mild dementia. Methods: A quasi‐experimental pre‐ and post‐test design with a non‐equivalent control group was used. Participants were 45 patients with mild dementia (experimental group = 22, control group = 23). In the experimental group, Fumanet exercise was performed 60 minutes per day, once per week for 8 weeks. Data were analyzed using descriptive statistics, t test, Chi‐square, Fisher's exact test, and two‐way repeated measures analysis of variance. Results: Gait ability in the experimental group was significantly improved compared with the control group (F = 9.08, P = .004). There were no significant differences in cognitive function or depression between the experimental and control groups. Although the intervention did not show a reduction in depression, participants exhibited a high participation rate and brighter mood with increasing sessions. Conclusions: It was confirmed that Fumanet exercise is an effective nursing intervention to improve gait ability among older adults with mild dementia.